Хазарский слой в Керчи - Айбабин, А.И. (Материалы по археологии, истории и этнографии Таврии, 2000)
В хазароведении одной из наиболее сложных и дискуссионных является проблема археологической культуры этнических хазар. В связи с этим, особый интерес представляет изучение средневековых слоев Керчи - византийского Боспора, где по сообщениям признанных достоверными письменных истшников с нзнапа VIII в. жили хазары. In Khazars study one of the most difficult, arising a lot of discussion problems is the one concerning revealing archaeological culture of the ethnic Khazars. Studying medieval stratums in Kerch - Byzantine Bosporos, where according to authentic written sources - Byzantine Theophanes and Nikephoros, the lives of John the Gothian and Jewish document of the 10th century kept in Cambridge- lived the Khazars beginning with the 8th century is of particular interest.